Breast arterial calcification is associated with incident atrial fibrillation among older but not younger post-menopausal women. Issue 2 (28th February 2023) - Iribarren, Carlos; Chandra, Malini; Parikh, Rishi V; Sanchez, Gabriela; Sam, Danny L; Azamian, Farima Faith; Cho, Hyo-Min; Ding, Huanjun; Molloi, Sabee; Go, Alan S
Abstract: Aims: The goal of this study was to examine the association of breast arterial calcification (BAC) presence and quantity with incident atrial fibrillation (AF) in a large cohort of post-menopausal women. Methods and results: We conducted a longitudinal cohort study among women free of clinically overt cardiovascular disease and AF at baseline (between October 2012 and February 2015) when they attended mammography screening. Atrial fibrillation incidence was ascertained using diagnostic codes and natural language processing. Among 4908 women, 354 incident cases of AF (7%) were ascertained after a mean (standard deviation) of 7 (2) years of follow-up. In Cox regression adjusting for a propensity score for BAC, BAC presence vs. absence was not significantly associated with AF [hazard ratio (HR) = 1.12; 95% confidence interval (CI), 0.89–1.42; P = 0.34]. However, a significant (a priori hypothesized) age by BAC interaction was found ( P = 0.02) such that BAC presence was not associated with incident AF in women aged 60–69 years (HR = 0.83; 95% CI, 0.63–1.15; P = 0.26) but was significantly associated with incident AF in women aged 70–79 years (HR = 1.75; 95% CI, 1.21–2.53; P = 0.003). No evidence of dose–response relationship between BAC gradation and AF was noted in the entire cohort or in age groups separately. Conclusion: Our results demonstrate, for the first time, an independent association between BAC and AF in women over age 70 years. Lay Summary: Epidemiological studies have shown that women with breast arterial calcification (BAC) in their mammograms are at increased risk of cardiovascular diseases including heart disease and stroke. However, it is not known at this time whether BAC is associated or not with development of atrial fibrillation, the most common type of heart rhythm abnormality. We recruited and followed over 7 years a cohort of 4908 postmenopausal women after they attended mammography screening. A total of 354 (7%) women went on to develop new-onset atrial fibrillation. When we considered the entire cohort, we did not find a significant association between the presence of BAC and atrial fibrillation, but when we examined the cohort according to the decade of age, we found that older women (70–79 years old) with BAC were at increased risk of atrial fibrillation (by ∼75%), whereas women 60–69 years old with BAC were not. These findings raise the possibility that BAC in mammograms can inform who to screen for atrial fibrillation in women 70 and older. Graphical Abstract: Graphical Abstract